Degenerate Four-Wave Mixing Experiments In Rose Bengal Dye Doped Gelatin Film. - Nooraldeen, Ahmad Y.; Jalal, Mohammed (Nahrain University College of Engineering Journal, 2008)
Optical phase-conjugation (OPC) was observed in Rose Bengal dye-doped gelatin films via Degenerate four-wave mixing (DFWM) using continuous wave of SHG of Nd-YAG laser radiation ( =532 nm) of total power 50 mW. Various parameters which influence the phase-conjugate (PC) signal during the DFWM process were studied. The PC signal contributions from induced holographic transmission and reflection gratings were measured. It observed a maximum PC beam reflectivity of 0.15% in these dye-doped gelatin films.